Acceptability of biologic treatments to patients undergoing rotator cuff repair - Brandon M. Wilde, BS; James M. Hotaling, MD; Corrine Welt, MD; Robert Tashjian, MD; Christopher D. Joyce, MD; Peter N. Chalmers, MD (JSES Reviews, Reports, and Techniques, 2025)
Background: The objective of this study was to determine the acceptability of biologic treatments for patients undergoing rotator cuff repair. Methods: This is a survey-based analysis of treatment acceptability of patients undergoing rotator cuff repair. Preoperatively, we collected demographics and survey responses. Patients were surveyed using a 5-point Likert scale regarding their willingness to undergo variations on biologic treatments for rotator cuff tears. These variations included frequency of treatment (daily, every other day, and weekly); duration of treatment (1, 3, and 6 months); side effect frequency (10%, 25%, 50%, and 75%); efficacy in terms of increased success rates (10% more, 20% more, and 30% more); and method of administration (injection, oral, and implantable). Descriptive statistical analysis was performed. Results: Fifty-five patients responded to the survey. The cohort was 65% male, with a mean ± standard deviation age of 60 ± 11 years, body mass index of 30 ± 7, and Charlson comorbidity index of 2 ± 1. With regards to frequency of treatment, 73% of patients either strongly agreed or agreed that they were willing to take a pill daily if it would increase the likelihood of success. For injections, 80% of patients either strongly agreed or agreed that they were willing to undergo an injection once, 71% weekly, 76% monthly, and 76% every 3 months. With regards to duration, 76% either strongly agreed or agreed that they were willing to take a medication for 1 month, 64% for 3 months, and 55% for 6 months. With regards to side effects, 47% either strongly agreed or agreed that they were willing to undergo a treatment with 10% side effects, 13% with 25% side effects, 7% with 50% side effects, and 7% with 75% side effects. With regards to efficacy, 73% either strongly agreed or agreed that they were willing to undergo a biologic treatment if it increased their success rates by even 10%. Conclusion: Based upon these survey responses, the biologic treatment options most acceptable to patients would be a pill or injection, administered for up to 3 months after surgery, with fewer than 10% of patients experiencing side effects. Most patients were willing to undergo a biologic treatment even if it only increased their likelihood of success by 10%. Therefore, based on these results, researchers and physicians developing biologic treatments could focus on avenues that only slightly increase success rates and can be administered within 3 months of surgery provided there is a favorable side effect profile.